Teaching English And Media Education - Siti Kurniati (Deiksis, 2013)
The media, especially television, is the main means of cultural transmission in our society and it is well attested fact that many students spend more hours in front of TV screen than they do in a class room Media education seeks to increase children’s critical understanding of the media – namely, television, film, radio, photography, popular music, printed materials, and computer software. How they work, how they produce meaning, how they are organised and how audiences make sense of them, and the issues that media education addresses. It aims to develop systematically children’s critical and creative powers through analysis and production of media artefacts. This also depends their understanding of the pleasure and enjoyment provided by the media. Media education aims to create more active and critical media users who will demand, and could contribute to, a greater range and diversity of media products.Key word: teaching English, media education